النووي في شرحه لصحيح مسلم - موساوي بلال; ضيفي اسماعيل ايوب; د/ قبلي بن هني (جامعة عمار ثليجي الاغواط, 2024)
ملخص: تناولنا في هذا البحث موضوع القواعد الأصولية للإمام النووي من خلال شرحه على صحيح مسلم باب الصيام وتهدف هذه الدراسة إلى إبراز بعض القواعد الأصولية التي بواسطتها يتمكن العلماء من استنباط الأحكام الفقهية من أدلتها التفصيلية، وذلك بتتبع المنهج التحليلي الوصفي مع ذكر خلاف العلماء في القاعدة وأقوالهم وقد تطرقنا في دراستنا إلى ترجمة للإمام النووي والإمام مسلم والتعريف بكتابي "المنهاج" و"صحيح مسلم" وخصصنا فصلا لدراسة القواعد الأصولية دراسة تأصيلية، وفي خاتمة البحث تم عرض أهم نتائج الدراسة وبعض التوصيات. كلمات مفتاحية: القواعد-الأصولية-النووي Abstract : In this research we have discussed the fundamentalist rules of Imam Al-Nawawi during his explanation of fasting chapter in Sahih Muslim, and our consideration aim to display some of the fundamentalist rules which through it the scientists can elicit the jurisprudential rulings from its detailed evidence,and that can happen by following the analytical qualitative method with mentioning the disagreement of scholars regarding the rule and their sayings. In our study, we dealt with a translation of Imam al-Nawawi and Imam Muslim and introduced the two books Al-Manhaj and Sahih Muslim and dedicated a chapter to the study of fundamentalist rules, and in the conclusion of the research, the most important results of the study and some recommendations were presented. Key words: rules, fundamentalism, Al-Nawawi.
باب الصيام انموذجا